2019
DOI: 10.1016/j.ijnss.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and turnover intention: Mediating effects of psychological empowerment of nurses

Abstract: Objective This study aims to determine the mediating effects of psychological empowerment on abusive supervision and turnover intention as perceived by nurses to provide information to change the status of nurse turnover. Methods A cross-sectional survey (a questionnaire examining perceptions of abusive supervision, measurement of psychological empowerment, and questionnaire for turnover intention) was used to collect data. A total of 1127 clinical nurses, who were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
64
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 14 publications
13
64
2
1
Order By: Relevance
“…The effect of this relationship should properly be determined through psychological empowerment of nurses. Unlike the study of Lyu, Ji, Zheng, Yu, and Fan (2019), the psychological empowerment of the nurses did not have a direct effect on job satisfaction and burnout and it was in line with the study of Yip (2004) who stated that the perception of empowerment differed in western and eastern societies because western culture supported espoused values in democratic culture and society. These conflicting research results may be due to the lack of consideration to the leader-member relationship in these studies.…”
Section: Discussionsupporting
confidence: 75%
“…The effect of this relationship should properly be determined through psychological empowerment of nurses. Unlike the study of Lyu, Ji, Zheng, Yu, and Fan (2019), the psychological empowerment of the nurses did not have a direct effect on job satisfaction and burnout and it was in line with the study of Yip (2004) who stated that the perception of empowerment differed in western and eastern societies because western culture supported espoused values in democratic culture and society. These conflicting research results may be due to the lack of consideration to the leader-member relationship in these studies.…”
Section: Discussionsupporting
confidence: 75%
“…Further, this result provided support to previous studies on nursing leadership where most nurses perceived their nurse managers as non‐abusive or non‐destructive leaders (Al‐Yami, Galdas, & Watson, 2018; El Dahshan, Youssef, Aljouaid, Babkeir, & Hassan, 2017). For instance, in a study involving 1,127 clinical nurses in China, nurse managers were evaluated by staff nurses as non‐abusive leaders (Lyu et al., 2019). A lower level of toxic behaviours among nurse managers is critically important considering the damaging effects that a toxic leader can have on an individual employee and the organisation (Yang, Yan, & Luo, 2017; Lavoie‐Tremblay et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It also elicits a desire to retaliate through decreased efforts at work (Cropanzano et al, 2017). In addition, DLB have been shown to be disempowering, as they tend to be associated with lower perceptions of psychological empowerment (i.e., meaning, autonomy, selfefficacy and impact at work; Lyu et al, 2019) among employees, a psychological state mediating the relation between supervisory behaviors and employees' behavioral empowerment efforts (Boudrias et al, 2009) Conversely, transformational leadership has been shown to help foster positive social exchanges between employees and supervisors (Wang et al, 2005), in turn leading to greater levels of energy, learning, and thriving among subordinates (Hildenbrand et al, 2018;Niessen et al, 2017). It has also been shown to fosters empowerment among employees and to sustain a desire to reciprocate via higher levels of behavioral efforts at work (Seibert et al, 2011).…”
Section: The Isolated Effects Of Petty Tyranny and Transformational Lmentioning
confidence: 99%